The new OECD Guidelines for Multinational Enterprises: better but not enough. Issue 6 (17th August 2016) - Reinert, Kenneth A.; Reinert, Oda T.; Debebe, Gelaye
ABSTRACT: This viewpoint addresses the extent to which the OECD Guidelines for Multinational Enterprises adequately serve as a system of global governance for MNEs. We argue that, while a 2011 revision has strengthened the Guidelines, their somewhat limited scope, voluntary nature, and less than satisfactory implementation render their potential utility unrealised.